A Construct Validity Of The Transferable Skills Scale For Assessment Of Career Guidance - Ahmad Rofi Suryahadikusumah; Akhmad Harum; Hera Yulia Prabiastuti (Bisma The Journal of Counseling, 2022)
Transferable skills are abilities and knowledge that can be used in various jobs and career paths and is related to the career development of students in the era of disruption. School counsellors need to understand student profiles related to these basic skill sets in order to be able to design career development programs that are relevant to today's career dynamics. This study aims to construct a transferable skill scale that can be used as a guidance and counselling assessment tool for student career development. The construction of this scale goes through the stages of 1) aspect construction based on literature studies, 2) item creation, and 3) pilot test. The construct validity test used Confirmatory Factor Analysis (CFA). The results of the CFA show that several dimensions of transferable skills require modification of the model until a fit model is obtained.. Thus the scale has a suitable model for measuring transferable skills, which consist of aspects of 1) Communication Skills (7 items), 2) Management Skills (9 Items), 3) Numerical Skills (5 Items), Creativity Skills (6 Items), Social Skills (6 Items), Critical Thinking Skills (5 Items), and Business Skills (6 Items).